DevOps benefits: A systematic literature review. (11th May 2022) - Faustino, João; Adriano, Daniel; Amaro, Ricardo; Pereira, Rubén; da Silva, Miguel Mira
Abstract: Among current IT work cultures, DevOps stands out as one of the most adopted worldwide. The focus of this culture is on bridging the gap between development and operations teams, enabling collaborative effort toward quickly producing software, without sacrificing its quality and support. DevOps is used to tackle a variety of issues; as such, there are differing benefits reported by authors when performing their analysis. For this research, we aim to reach consensus on the DevOps benefits reported in existing literature. To accomplish this objective, two systematic literature reviews. The first intends to find all benefits reported in the literature, while the second review will be used to map the benefits found in the first one with DevOps implementation case studies, providing empirical evidences of each benefit. To strengthen the results, the concept‐centric approach is used. During this research it was possible to observe that the most reported benefits are aligned with the DevOps premises of better collaboration between developers and operators, delivering software and products quicker. Based on DevOps implementation case studies, most reported benefits include a faster time to market as well as improvements in synergy and automation. Less reported benefits include a reduction in failed changes and security issues.